Influence of Body Composition on the Perioperative and Survival Outcomes of Renal Cell Carcinoma - Edouard H. Nicaise; Benjamin N. Schmeusser; Yash B. Shah; Mehmet A. Bilen; Kenneth Ogan; Viraj A. Master (Journal of Urologic Oncology)
The purpose of this review is to provide an up-to-date understanding of the literature describing the impact of body composition on renal cell carcinoma (RCC) prognosis and outcomes. Although obesity is recognized as a risk factor for RCC development, overweight patients with localized and advanced RCC display more favorable outcomes than normal-weight individuals. However, obesity as measured by body mass index is a poor indicator of total body fat, fails to account for lean muscle mass, and inconsistently predicts perioperative and survival outcomes in RCC. Recent studies have suggested that objective measurements of lean and fat body masses from various compartments have strong prognostic utility. Low muscle mass (i.e., sarcopenia) and low visceral adiposity are often associated with poorer survival outcomes in localized and advanced RCC. These patients tend to experience higher rates of recurrence, progression, treatment failure, and death from kidney cancer. Given the influence of body composition in RCC outcomes, further characterization of the role of prehabilitation programs is warranted to evaluate the feasibility and efficacy of interventions targeting these modifiable factors.